Chromatographic and computational screening of anisotropic lipophilicity and pharmacokinetics of newly synthesized 1-aryl-3-ethyl-3-methylsuccinimides. (February 2020) - Kovačević, Strahinja; Banjac, Milica Karadžić; Podunavac-Kuzmanović, Sanja; Milošević, Nataša; Ćurčić, Jelena; Vulić, Jelena; Šeregelj, Vanja; Banjac, Nebojša; Ušćumlić, Gordana
Graphical abstract: Highlights: A set of newly synthesized succinimides was analyzed by RP-HPLC and RP-HPTLC. Chromatographic lipophilicity (ChL) of the studied derivatives was determined. Correlations between their ChL and pharmacokinetic parameters were defined. Their ability to pass the blood-brain barrier and other ADMET features were estimated. Some of the analyzed succinimide derivatives have high potential to become anticonvulsant candidates. Abstract: The present study is focused on a series of newly synthesized 1-aryl-3-ethyl-3-methylsuccinimide derivatives, as potential anticonvulsants. The retention behavior of eleven succinimide derivatives was determined by using reversed phase high performance liquid chromatography (RP-HPLC) and reversed phase high performance thin layer chromatography (RP-HPTLC). The estimated retention behavior was correlated with partition (log P ) and distribution coefficients (log D ). These high correlations pointed out that the determined retention parameters (log k 0 and R M 0 ) can be considered chromatographic (anisotropic) lipophilicity of the studied succinimide derivatives. The structural properties, which dominantly affect the chromatographic lipophilicity, were determined as well. The significant correlations between the chromatographic lipophilicity and plasma protein binding (PPB), Madin-Darby Canine Kidney (MDCK) cells permeability, volume of distribution (Vd) and absorption constant (Ka) indicate the strong influence of lipophilicity on pharmacokinetics of 1-aryl-3-ethyl-3-methylsuccinimide derivatives. These derivatives have also been tested applying Comprehensive Medicinal Chemistry (CMC) drug-like rules which confirmed their drug-like properties. Besides, their blood-brain penetration (BBB) ability has been estimated applying the set of Clark's rules and by using Pre-ADMET software. Regarding toxicity, it was predicted that only one compound from the set might have toxic effects by blocking the hERG potassium channel. The present study reveals which molecular features in the structure of novel succinimide derivatives could be crucial for their lipophilicity, and consequently for their pharmacokinetic properties. The results indicate that the newly synthesized series of succinimide derivatives should be further considered in design of novel anticonvulsants.